Achieving Digestive Autonomy and Gastrointestinal Continuity in a Patient with Short Bowel Syndrome Secondary to Concomitant Jejunal Atresia and Small Intestinal Hirschsprung's Disease - Velasquez, Alejandro R.; Xu, Thomas O.; Liu, Yu-Ting; Kidwai, Sulaiman; Russell, Teresa L.; Tiusaba, Laura; Artis, Krystal; Sandler, Anthony; Badillo, Andrea; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2024)
Concomitant presentation of jejunal atresia and Hirschsprung's disease is rare and places children at high risk for developing short bowel syndrome and parenteral nutrition dependence, which can affect the feasibility/timing of pull-through. A patient was born with jejunal atresia with a delayed diagnosis of Hirschsprung's disease. After several procedures and bowel resections, the patient was ultimately left with an end jejunostomy and long Hartman's pouch with short bowel syndrome, dependent on parenteral nutrition. The patient initially presented to our institution at age 2 with failure to thrive secondary to an obstructed/dilated jejunostomy and mild enterocolitis of their defunctionalized segment. The patient subsequently underwent completion of subtotal colectomy and revision of jejunostomy utilizing a serial transverse enteroplasty to manage the dilated bowel and gain length. The patient was able to wean off parenteral nutrition and achieve nutritional autonomy by age 5. Following this, the patient was able to undergo an ileoanal pull-through. After the pull-through, the patient was able to pass stool independently and suffered no major complications to date. Serial transverse enteroplasty can be successfully utilized in patients with a history of Hirschsprung's disease and jejunal atresia to achieve nutritional autonomy and ultimately reestablish gastrointestinal continuity with pull-through.
Keywords: STEP procedure; total colonic Hirschsprung's disease; short bowel syndrome; Hirschsprung's pull-through; jejunal atresia